Lower Limb Resistance Training in Individuals With Parkinson's Disease: An Updated Systematic Review and Meta-Analysis of Randomized Controlled Trials - Li, Xiaoyan; He, Jie; Yun, Jie; Qin, Hua (Frontiers in Neurology, 2020)
Objective: Initial randomized controlled trials (RCT) and recently released systematic reviews have identified resistance training (RT) as a modality to manage motor symptoms and improve physical functioning in individuals with Parkinson’s disease (PD), although the effects are inconsistent. Therefore, we conducted an updated meta-analysis to reassess the evidence of the relationship. Methods: We performed a systematic search of studies reporting the effects of RT in PD available through major electronic databases (PubMed, Medline, Embase, Ovid, Cochrane Library, CNKI, Wanfang) through 20 July 2020. Eligible RCTs were screened based on established inclusion criteria. We extracted data on the indicators of leg strength, balance, gait capacity, and quality of life (QoL) of lower limbs. Random and fixed effects models were used for the analysis of standard mean differences (SMD) or mean differences (MD) with their 95% confidence intervals (CI). Results: Thirty-one papers from 25 independent trials compromising 1239 subjects were selected for eligibility in this systematic review and meta-analysis. Summarized data indicated that the leg strength increased statistically significant in PD patients(SMD = 0.79, 95% CI 0.3, 1.27, P = 0.001), the balance capability was improved statistically significant in PD patients(SMD = 0.34, 95% CI 0.01, 0.66, P = 0.04), and QoL statistically significantly improved (MD = -7.22, 95% CI -12.05, -2.39, P = 0.003). For gait performance, four indicators were measured, the results as follows: fast gait velocity(MD = 0.14, 95% CI 0.06, 0.23, P = 0.001), Timed-up-and-go-test (TUG, MD = -1.17, 95% CI -2.27, -0.08, P = 0.04) and Freezing of Gait Questionnaire(FOG-Q, MD = -1.74, 95% CI -3.18, -0.3, P = 0.02) were improved statistically significant across trials, while there were no statistically significant improvement in stride length(MD = -0.05, 95% CI -0.12, 0.02, P = 0.15) in PD patients. Conclusions: Lower limb RT has positive effects during rehabilitation in individuals with PD in leg strength, QoL, and improve gait performance to a certain extent. RT also could improve balance capacity of patients, although a wide variety of tools were used, and further study is needed to confirm these findings.